GRP137 promotes cell proliferation and metastasis through regulation of the PI3K/AKT pathway in human ovarian cancer. Issue 5 (October 2018) - Zhang, Li-qian; Yang, Su-qing; Qu, Xiang-dong; Chen, Xian-jun; Lu, Hong-sheng; Wang, Ying
Purpose: Ovarian cancer is one of the leading causes of death for women worldwide. The present study aims to investigate the role of G protein-coupled receptor 137 (GPR137) in the biological activities of ovarian cancer cells. Methods: (QUERY: Please supply Methods for Abstract) Results: G protein-coupled receptor 137 was highly expressed in clinical ovarian cancer tissues and exhibited the highest protein levels in SKOV3 cells and OVCAR3 cells. Knockdown of GPR137 caused significant decreases in cell proliferative rates and colony formation abilities in SKOV3 cells and OVCAR3 cells and also inhibited the in vivo tumorigenesis in a xenograft model. It was observed that knockdown of GPR137 inhibited cell motility by up to 40% in SKOV3 cells and approximately 65% in OVCAR3 cells in wound-healing assay. Cell migration abilities were consistently inhibited by 68.2% in SKOV3 cells and 59.3% in OVCAR3 cells, whereas cell invasion abilities were inhibited by 64.0% and 74.2% in SKOV3 and OVCAR3 cells, respectively, after knockdown of GPR137. When GPR137 was depleted, epithelial markers were increased, while mesenchymal markers decreased. Conclusions: Our data suggest that GPR137 plays pro-oncogenic roles in ovarian cancer via regulation of the PI3K/AKT pathway. These observations might pave new insights into therapeutic strategies against human ovarian cancer.